Performance evaluation of enhanced MANETs routing protocols under video traffics, for different mobility and scalability models using OPNET - Ahmed, Diaa Eldein Mustafa; Khalifa, Othman Omran (American Journal of Engineering Research (AJER), 2017)
Mobile Ad hoc Networks (MANETs) is a type of wireless networks which consist of a collection of wireless mobile nodes forming a self-configured and self-organized network without any need for using existing infrastructure or centralized administration. Recently video streaming over MANETs technology received a huge attention from the researchers and industry sectors to make them more affordable better and valuable in a communication environment. Routing becomes a curtail core problem in networks for sending data from source node to destination node. There are several routing protocols algorithms are proposed recently to overcome most of the MANETs challenges such as high dynamic topology changes, limited resources(bandwidth ,memory ,CPU), link failure caused by node mobility, limited battery power on mobile nodes, energy consumption due to routing computation and etc. The main method for evaluating the performance of MANETs is simulation. This paper provides a comprehensive study and analysis of the performance evaluation of various MANETs routing protocols such as AODV, OLSR, DSR, TORA, and GRP, under video traffic over IEEE 802.11/g. Performance evaluation under various network scenarios for video streaming performed on the basis of the performance metrics (end to end delay, throughput, packet delivery ratio (PDR), routing overhead, packets dropped, retransmission attempt and network load). The objective of the performance evaluation is to show the effect of the mobility and scalability models on the overall performance of video transmission on the MANETs routing protocols and which protocols overcome the video streaming challenges. Different mobility and scalability scenarios are evaluated after simulation of network with the help of OPNET modeler simulator